2011
DOI: 10.2298/hel1155101h
|View full text |Cite
|
Sign up to set email alerts
|

Gene effect, combining ability and heterosis in sunflower morphophysiological traits

Abstract: Four interspecies populations, originating from three annual (H. debilis, H. praecox, H. deserticola) and one perennial (H. resinosus) wild species, were used to produce 13 new (cms) inbred lines with cytoplasmic male sterility, three Rf restorer lines with good general combining ability used as testers and their F 1 hybrids. A two-year trial with three replicates was set up using the line × tester method. The inbred A-lines, Rf-testers and F 1 hybrids differed significantly in the mean values for both studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…So, cross 12-A × 20-R appeared to be a good specific combiner for no. of leaves/plants as shown in Table4 Hladni et al (2011),Imran et al (2015),Iqbal et al (2018). also reported the same results for no.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…So, cross 12-A × 20-R appeared to be a good specific combiner for no. of leaves/plants as shown in Table4 Hladni et al (2011),Imran et al (2015),Iqbal et al (2018). also reported the same results for no.…”
supporting
confidence: 63%
“…Cross 23-A × 20-R exhibited as good specific combiner for achene yield/plant among crosses as shown in Table 4. Hladni et al (2011), Imran et al (2015), Singh et al (2017, Lakshman et al (2019) also reported similar findings.…”
Section: Time To Maturitymentioning
confidence: 58%
“…Ghaffari et al (2011) reported similar results, although their figures were on the upper side, up to 48% oil content. The difference can be attributed to the fact that their work used a different set of germplasm and environments as reported by Hladni et al (2008) and Rondanini et al (2003). However, five of these hybrids were not significantly different from the highest oil content check variety CH3 (Table 1).…”
Section: Agronomic Performance Of Top-cross Hybridsmentioning
confidence: 88%
“…Seed oil percentage of 38% to 54.4% and protein percentages of 15% to 17% have also been reported (Keshta et al, 2008). However, these traits have been reported to be influenced by the germplasm and the environment in which they were evaluated (Hladni et al, 2008;Rondanini et al, 2003). This means that values recorded from elsewhere cannot be generally applied although they might be from the same germplasm set.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation